Holddeling: Når der gøres maskulinitet og hvidhed - Kofoed, Jette (Kvinder, Køn & Forskning, 2005)
This article follows a group of 13 year-old boys’ daily selection of football-teams in the schoolyard. The outcome of this repeated practice seems to be identical, i.e. the same teams are selected over and over again. Yet the boys repeat the ritual of selection. It is an empirical investigation based on a fieldwork in a 6th grade in a Copenhagen public school. The analytical focus is on how social categories such as whiteness, masculinity, and age intersect and how the intersection intertwines with other empirically relevant categories such as normality, pupilness, and (in)appropriatedness. Exploring this particular ritual of teamselection the taken-for-granted practices and understandings of teams and football among the schoolboys is explored. The analysis follows the lines of reasoning into practices of inclusion and exclusion and the relationships between the larger groups of pupils. This reading shows how understandings and practices from this particular ritual of selecting teams mingles into wider relationships and how the outcome of the ritual lends meaning to other social practices. A number of components interact in the daily processes of doing pupilness and in the analysis it becomes apparent that the requirements of appropriated pupilness can be met in a number of ways.